2008
DOI: 10.3748/wjg.14.4280
|View full text |Cite
|
Sign up to set email alerts
|

Role of cytokines in inflammatory bowel disease

Abstract: Inflammatory bowel disease (IBD), which includes Crohn's disease (CD) and ulcerative colitis (UC), represents a group of chronic disorders characterized by inflammation of the gastrointestinal tract, typically with a relapsing and remitting clinical course. Mucosal macrophages play an important role in the mucosal immune system, and an increase in the number of newly recruited monocytes and activated macrophages has been noted in the inflamed gut of patients with IBD. Activated macrophages are thought to be ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
489
1
11

Year Published

2009
2009
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 579 publications
(517 citation statements)
references
References 91 publications
16
489
1
11
Order By: Relevance
“…Inflammatory macrophages are known to produce an array of cytokines and chemokines that promote infiltration and activation of other leukocytes, including lymphocytes, and that also promote angiogenesis, cell proliferation, and tissue damage. 43,44 However, unlike IL-10 Ϫ/Ϫ mice, in which malignant tumors develop in the inflamed intestine, 9 no tumors were reported in mice with LysM-or Mx1-Cre-mediated Stat3 inactivation in myeloid cells. In contrast, we demonstrate the development of malignancy in Stat3-IKO mice, suggesting that Stat3 in both myeloid and lymphoid cells may serve as a control point for the development of malignant intestinal tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Inflammatory macrophages are known to produce an array of cytokines and chemokines that promote infiltration and activation of other leukocytes, including lymphocytes, and that also promote angiogenesis, cell proliferation, and tissue damage. 43,44 However, unlike IL-10 Ϫ/Ϫ mice, in which malignant tumors develop in the inflamed intestine, 9 no tumors were reported in mice with LysM-or Mx1-Cre-mediated Stat3 inactivation in myeloid cells. In contrast, we demonstrate the development of malignancy in Stat3-IKO mice, suggesting that Stat3 in both myeloid and lymphoid cells may serve as a control point for the development of malignant intestinal tumors.…”
Section: Discussionmentioning
confidence: 99%
“…The effects of Phe on cytokine expression are likely due to Phe affect the proliferation of immune cells. In human, lymphocytes can secret IL-10 and TGF-b [53]. Chuang et al [54] reported that Phe is essential for lymphocyte proliferation in humans.…”
Section: Phe Improved the Intestinal Innate Immune Responsementioning
confidence: 99%
“…Multiple hereditary, environmental, microbiological and immunological factors are believed to contribute to the pathogenesis of UC (7,8). Immunoregulatory and pro-inflammatory cytokines appear to play a significant role in UC (9). Immunomodulating agents and corticosteroids have been used to treat UC, although not always with positive outcomes (10 cated that N3PUFAs could be efficient in the treatment of inflammatory bowel diseases, which would decrease the need for steroids and prevent the recurrence of UC and Crohn's disease (CD) (11).…”
Section: Introductionmentioning
confidence: 99%